Comparison of access to medicines between Klang Valley and East Coast of peninsular Malaysia for children living in poor households - Saiful A.; Ithnin M.; Mohd Rani M.D.; Mohamed I.N.; Al-Naggar R.; Khairun Nain Nor Aripin; Nor Azila Noh; Nazefah Abdul Hamid (University of Benin, 2024)
Purpose: To compare access to medicines in children living in poor households (income of USD1/person/day) between urbanised Klang Valley and rural East Coast of Peninsular Malaysia. Methods: A semi-structured interview was conducted with caregivers to determine demographics, access to medicines, knowledge, attitude and practice of parents in obtaining medicines for children. Results: There was no significant difference socio-demographically between poor households in Klang Valley (N = 58) and East Coast (N = 40). The study found that access to medicine for children (N = 325) in the households was adequate, where all households that reported illness in the children over the last 1 month and the last 6 month periods, obtained medicines and 99 % of the children were fully immunized. Qualitative analysis showed that poor households face several barriers in accessing medicines for their children such as financial, transportation, physical and attitudinal. Conclusion: Access to medicines for children living in poor households in both areas were similar and adequate. However, barriers to access remain and further studies are required. Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, 300001 Nigeria. All rights reserved.